2012
DOI: 10.1002/kin.20746
|View full text |Cite
|
Sign up to set email alerts
|

Purification of chloroperoxidase from Musa paradisiaca stem juice

Abstract: Chloroperoxidase from Musa paradisiaca stem juice has been purified to homogeneity using a concentration obtained by ultrafiltration and anion exchange chromatography on diethylaminoethyl (DEAE) cellulose. The purified enzyme gave a single protein band in SDS-PAGE analysis corresponding to molecular mass of 43 kDa. The native PAGE analysis result has also given a single protein band, confirming the purity of the enzyme. The purified enzyme was chlorinated and brominated with monochlorodimedone, the substrate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…In the range 40-60°C, the process of thermal inactivation begins although the enzymatic activity does not decrease significantly. The results obtained for POD from plums are in accordance with the study of Yadav et al [26] who investigated the POD from banana (Musa paradisiaca) in the 15-35°C temperature range, and reported the optimum temperature of 25°C. In contrast, Rani and Abraham [15] determined the optimum temperature of 55°C for the activity of POD from Eupatorium odoratum, whereas Pandey and Dwivedi [4] studied POD from papaya and assessed an optimum temperature of 40°C.…”
Section: Effect Of Ph and Ph Stabilitysupporting
confidence: 90%
“…In the range 40-60°C, the process of thermal inactivation begins although the enzymatic activity does not decrease significantly. The results obtained for POD from plums are in accordance with the study of Yadav et al [26] who investigated the POD from banana (Musa paradisiaca) in the 15-35°C temperature range, and reported the optimum temperature of 25°C. In contrast, Rani and Abraham [15] determined the optimum temperature of 55°C for the activity of POD from Eupatorium odoratum, whereas Pandey and Dwivedi [4] studied POD from papaya and assessed an optimum temperature of 40°C.…”
Section: Effect Of Ph and Ph Stabilitysupporting
confidence: 90%
“…() and Yadav et al . () also reported that peroxidase had an optimum temperature of 25C. The enzyme from lettuce stem showed an optimum temperature of 45C (Hu et al .…”
Section: Resultsmentioning
confidence: 95%
“…These enzymes include Peroxidase, Chloroperoxidase, Lignin peroxidase, Mnperoxidase [9] and catalase [10] that isolated from specific plants viz. soybean [11], horseradish, radish [12], and their materials such as seeds [13], leaves [14], stem [15], roots [16]. Tyrosinase and Laccase [9] are obtained from different fungal species.…”
Section: Introductionmentioning
confidence: 99%